The Implementation of Training Needs Analysis (TNA) : A Study in Malaysian Banks and Financial Institutions - Siti Fatimah, Abdullah (2010)
This study seeks to review how banks and financial institutions approached their TNA. In conjunction with that, the study had examined many aspects of the TNA practices of organizations such as procedures for selecting training participants, methods for gathering data, techniques employed and whether the three levels of analysis (organizational, operational and individual) were employed in organizations TNA practices. A quantitative research method was employed. Survey data was obtained from fifty six HRM practitioners in banks and financial institutions in Malaysia, listed in the directory of Bank Negara Malaysia. The results of this study revealed that the organizations implemented systematic procedures for selecting training participant with involvement of multiple parties. These organizations also adopted some formal data collection methods and techniques to analyze their training needs. The results of the study also discovered that all three levels of TNA analysis namely organizational, operational and individual analysis were conducted although the types of techniques that they used were only involved minimal analysis. The study found no significant differences in TNA practices of banks and financial institutions and as well as size of organizations . However, organizations of dissimilar nationality of parent companies were significantly different in terms of used of TNA methods like KSA test and Delphi method. Low correlations were found between organizations’ length of operations with most of data collection methods and TNA techniques. This study contributes to HR practice in several ways. First, it conforms that HRM or HRD practitioners do recognize the importance and power of effective TNA in helping them plan and strategize for effective HRM or HRD activities. Second, it observes a lack of effective resources to help HRM or HRD practitioners in conducting training needs assessment in their organizations.